Diagnosing the Dimensions of Marketing Creativity: An exploratory Study of the Opinions of a Sample of Retailers at Al-Wazir Detergent Manufacturing Company in Kirkuk Governorate (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The research aimed to diagnose the dimensions of marketing creativity, which are (creativity in the product, creativity in pricing, creativity in promotion, creativity in distribution), and to introduce them to retailers in the Al-Wazir Detergents Manufacturing Company in Kirkuk Governorate. The research problem was represented by the following question: Do they have Are the retailers in the company sufficiently and clearly aware of the dimensions of marketing creativity? To answer this question, a main hypothesis was adopted, which states: “The retail traders surveyed in the company have sufficient awareness, a clear vision, and precise knowledge of the dimensions of marketing creativity directed at them and prevailing in their company.” And to prove The validity or otherwise of this hypothesis was tested statistically, using appropriate statistical tools, through a questionnaire prepared and distributed for this purpose, as (75) questionnaires were distributed to a purposive sample represented by elite retailers dealing with the company under investigation, and it was fully recovered. That is, a percentage of (100%). The answers of the respondents were analyzed, which enabled the researchers to present a set of results, the most important of which were , Through presenting, diagnosing, and analyzing the opinions of the surveyed sample, it was revealed that they were adequately aware of the dimensions of marketing creativity adopted by the surveyed company. The response of the respondents to the standards (creativity in the product, creativity in pricing, creativity in promotion, creativity in distribution) was positive, and at a high level for all. This is due to the importance of the marketing mix for the products manufactured by the company, and the role of the marketing mix in building a positive image and a distinguished position among retailers and customers at the same time      The research also presented a set of proposals for the researched company, including :Employing the positive results of the elements of the marketing mix that ranked first, and addressing the elements that came in last ranks to ensure higher marketing creativity through the elements of the marketing mix.